Alexa, what was an archive? - Delgado Gómez, Alejandro; Casellas i Serra, Lluís-Esteve; Hernández Olivera, Luis M. (Tábula, 2021)
The evolution of the Archival Science has often taken place in difficult times, because of the frequent social, economic, cultural and political crises which it has encountered and which as well, have helped to shape it, not allowing us however, to speak of a crisis typical of the Archival Science. After all, it must be difficult to begin a construction in the course of different revolutions, some world wars, the emergence of the contemporary avant-garde, the crisis of ‘29, the disappearance of the Big Science, the emergence of various countercultures, the expansion of democracy or sexual liberation: it might be regarded as an abrupt birth, but not because it would be involved in such crises, but because of its ability to be immersed in the richness of those around it.